2014
DOI: 10.5812/ircmj.13628
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Second and Third Generations Combined Oral Contraceptive Pills’ Effect on Mood

Abstract: Background:Most women taking combined oral contraceptives (COCs) are satisfied with their contraceptive method. However, one of the most common reasons reported for discontinuation of combined oral contraceptives (COCs) is mood deterioration.Objectives:This study aimed to compare effects of the second and third generation oral contraceptive pills on the mood of reproductive women.Materials and Methods:This randomized, double-blind, controlled clinical trial was conducted in reproductive women at health centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
(21 reference statements)
1
19
0
Order By: Relevance
“…This suggests that EE-LNG is more likely to cause mood swings and vaginal dryness compared to EE-DSG. These findings are consistent with those of previous studies that state that third-generation contraceptive pills have better effects on women's mood swings compared to secondgeneration ones [26].…”
Section: Impaired Sexual Intercoursesupporting
confidence: 83%
“…This suggests that EE-LNG is more likely to cause mood swings and vaginal dryness compared to EE-DSG. These findings are consistent with those of previous studies that state that third-generation contraceptive pills have better effects on women's mood swings compared to secondgeneration ones [26].…”
Section: Impaired Sexual Intercoursesupporting
confidence: 83%
“…Longitudinal and cross-sectional studies assessing contraceptionrelated mood changes have yielded inconsistent results. The use of hormonal contraceptives was found to be associated with increases, decreases or no overall change in negative affect (Gingnell et al, 2013;Jarva and Oinonen, 2007;O'Connell et al, 2007;Oinonen and Mazmanian, 2002;Ott et al, 2008;Rosenberg and Waugh, 1998;Shahnazi et al, 2014;Svendal et al, 2012). It is unclear whether the inconsistency of findings reflects actual differences between women in their mood-related responses to hormonal contraceptives, or whether they are due to differences in study design or pill types (Pletzer and Kerschbaum, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have suggested differences in the incidence of mood change between COC formulations (EE dose316, progestogen type336) no consistent trends have been reported. It is possible that formulations containing an anti-androgenic progestogen such as drospirenone337,338 could have a more beneficial effect on mood than preparations containing other progestogens.…”
Section: Side Effects Associated With Chc Usementioning
confidence: 99%